2016
DOI: 10.1001/jamapsychiatry.2016.1232
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin for Treatment of Overweight Induced by Atypical Antipsychotic Medication in Young People With Autism Spectrum Disorder

Abstract: clinicaltrials.gov Identifier: NCT01825798.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 40 publications
1
72
0
1
Order By: Relevance
“…A recent meta-analysis of adults has indirectly demonstrated that the amount of weight loss due to lifestyle interventions may be similar to that provided by use of pharmaceutical agents (9). Though contradictory findings exist, including a study (10) in which medication alone was more effective for weight loss than behavioral interventions, it is possible that this study reflects the difficulty of many psychiatric patients to adhere to strict dietary guidelines or exercise regimens, including those used in behavioral interventions (10, 11). This is one reason that medications like metformin are being studied.…”
Section: Evidence For Lifestyle Interventions For Weight Lossmentioning
confidence: 93%
See 3 more Smart Citations
“…A recent meta-analysis of adults has indirectly demonstrated that the amount of weight loss due to lifestyle interventions may be similar to that provided by use of pharmaceutical agents (9). Though contradictory findings exist, including a study (10) in which medication alone was more effective for weight loss than behavioral interventions, it is possible that this study reflects the difficulty of many psychiatric patients to adhere to strict dietary guidelines or exercise regimens, including those used in behavioral interventions (10, 11). This is one reason that medications like metformin are being studied.…”
Section: Evidence For Lifestyle Interventions For Weight Lossmentioning
confidence: 93%
“…Multiple mechanisms have been proposed for its effect on weight loss. These include its ability to decrease insulin resistance (reversing the insulin resistance caused by antipsychotics) and reduce hepatic glucose production (11, 12). While multiple RCTs and meta-analyses show metformin to be moderately beneficial for promoting weight loss in adults using antipsychotics, others found no weight loss benefits (1315).…”
Section: Metformin As a Medication For Weight Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas most of the studies reviewed in earlier sections reported that metformin was well tolerated, 1 study 14 reported significantly more adverse events with metformin; the commonest adverse event was gastrointestinal disturbance, something that is well known. The use of an extended-release formulation may improve the tolerability of the drug.…”
Section: Safety and Tolerabilitymentioning
confidence: 97%